The Effectiveness of Spritual Emotional Freedom Technique (SEFT) Therapy to Increase Motivation to Memorize the Quran and Reinforcement of Students at the Baitul Ilmi Tahfidz Putri Islamic Boarding School in Bima City - Qothiyah, Nely Ilmi; Luthfiyah, Luthfiyah; Syarifuddin, Syarifuddin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2025)
This study explores whether the application of Spiritual Emotional Freedom Technique (SEFT) therapy can effectively enhance the motivation and reinforcement of students in memorizing the Qur’an at the Baitul Ilmi Female Tahfidz Islamic Boarding School in Bima City. To investigate this issue, the study utilized a quantitative research approach with a one-group pretest-posttest design. The participants consisted of 16 ninth-grade students from the Baitul Ilmi Female Tahfidz Islamic Boarding School. Data were gathered using standardized instruments measuring motivation and reinforcement, and subsequently analyzed through a series of statistical procedures, including normality testing, paired samples t-test, and Pearson correlation analysis. The findings revealed that the data were normally distributed, and there was a statistically significant increase in both motivation and reinforcement after SEFT therapy was applied (p < 0.001). Descriptively, students showed greater enthusiasm in attending tahfidz activities, became more confident in memorizing, and were more emotionally resilient. Reinforcement was reflected through improved self-perception, responsiveness to praise, and consistency in memorization practices. However, the correlation analysis showed no significant relationship between motivation and reinforcement (r = -0.079; p = 0.771), indicating that while both improved independently, they were not directly linked statistically. These results suggest that SEFT therapy is effective in enhancing students’ psychological and emotional readiness for Qur'anic memorization, though the effects on motivation and reinforcement function separately